Republican monarchy in the 1830 revolutions: from Lafayette to the Belgian Constitution. Issue 7 (3rd October 2019) - Deseure, Brecht
ABSTRACT: The Belgian Constitution of 1831 marked a decisive step in the continental evolution from Restoration constitutional monarchy, based on the monarchical principle, towards the establishment of parliamentary constitutional monarchy. At the time, the new balance of power desired by the Belgian revolutionaries was captured by the phrase 'republican monarchy'. It is remarkable that this concept, despite being so central to the founding fathers' deliberations, has hardly been commented upon by later historians and public lawyers. This article aims to reconstruct the origin, meaning and uses of this concept in the context of the 1830 revolutionary wave. French revolutionary veteran general Lafayette was responsible for popularizing republican monarchy in the July Revolution, although the term's origins went back to eighteenth-century debates on the reform of absolute monarchy. Lafayette used it to summarize the institutional demands of the republican movement vis-à-vis king Louis Philippe . Its transnational migration to the Belgian context subsequently entailed a shift in meaning which will be charted through an analysis of the Belgian constituent and public debates. Finally, the reasons for the concept's sudden disappearance from the political stage will be addressed.